2021
DOI: 10.1017/s1368980021001270
|View full text |Cite
|
Sign up to set email alerts
|

Organic food consumption is associated with a healthy lifestyle, socio-demographics and dietary habits: a cross-sectional study based on the Danish Diet, Cancer and Health cohort

Abstract: Objective: To study the association between organic food consumption and lifestyle, socio-demographics, and dietary habits. Design: Cohort participants completed detailed questionnaires about organic food consumption, diet, and lifestyle between 1999 and 2002. Polytomous logistic regression models were used to estimate the association between organic food consumption, and lifestyle, socio-demographics, and dietary habits. Setting: This cross-sectional study uses data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Researchers have investigated the role of various lifestyle variables in consumer behaviour in response to numerous situations in which even life-cycle data could not explain why two households with identical demographic profiles might exhibit radically different behaviour in the marketplace (Gunter and Furnham, 2014;Grunert, 2019). Andersen et al (2022) examined the influence of lifestyle on organic food consumption in more detail. The follow-up also included questions regarding eating habits, smoking/non-smoking, physical activity, but also questions such as BMI.…”
Section: Healthy Lifestyle and Socio-demographic Factorsmentioning
confidence: 99%
“…Researchers have investigated the role of various lifestyle variables in consumer behaviour in response to numerous situations in which even life-cycle data could not explain why two households with identical demographic profiles might exhibit radically different behaviour in the marketplace (Gunter and Furnham, 2014;Grunert, 2019). Andersen et al (2022) examined the influence of lifestyle on organic food consumption in more detail. The follow-up also included questions regarding eating habits, smoking/non-smoking, physical activity, but also questions such as BMI.…”
Section: Healthy Lifestyle and Socio-demographic Factorsmentioning
confidence: 99%
“…The Sustainability Diet Index 36 is a score with a maximum of 20 points summed up using four subindices encompassing environmental, nutritional, economic, and sociocultural aspects. Kesse‐Guyot et al utilized an Organic Score ranging between 0 and 32 points across 18 food groups, and Andersen et al 34 used an overall organic food score ranging from 6 to 24 points. Gosling et al 33 used both a food propensity questionnaire and a 24HR to investigate frequency of organic food consumption across 12 food groups.…”
Section: Resultsmentioning
confidence: 99%
“…All studies used standard BMI categories according to the WHO as outcome variables. The number of adjustment factors varied between 6 22 and 15 33,34 variables per study (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from a descriptive study conducted in Germany demonstrated that most organic food consumers exhibit lower body weight than non-consumers [ 26 ]. In addition, a recent Danish study observed that people with generally healthy lifestyles, physical activities, and dietary habits were more likely to eat organic food [ 27 ]. Recent studies on organic food consumption have also highlighted that people turned to organic food due to concerns about the potentially harmful effects of pesticide residues on consumer health [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%